The Effect of Using Some Futsal Skills On Decreasing ADHD Level in Children Aged 11 – 12 Years Old - Qutaiba, Lubna (Journal of Physical Education, 2017)
The aim of the research is to identify the effect of using futsal skills on reducing ADHD levels in children aged 11 – 12 years old. The researcher hypothesized significant statistical differences between pre and posttests in both groups. The researcher used the experimental method. The subjects were divided into two equal groups; experimental and controlling group. The data was collected and treated using proper statistical operations. The researcher concluded that futsal skills reduced ADHD in some pupils and injuries in some pupils. Finally she recommended adding motor games to reduce ADHD in children